Toward Measuring Soft Skills for Youth Development: A Scoping Study - Allan B. I. Bernardo; Jose Ramon G. Albert; Jana Flor V. Vizmanos; Mika S. Mu\~noz (Philippine Institute for Development Studies (PIDS), 2023)
Rapid technological advancements and shifting economic paradigms in the 21st century also continuously change the nature of work wherein more complex and sophisticated skill sets are being required. There is a growing recognition of the pivotal role soft skills play in preparing the youth for this evolving environment. However, there remains a notable gap in identifying what comprises these soft skills, or Transversal Competencies (TVC). The study aims to contribute to policy discussions to support the government in enhancing its understanding of soft skills building and in formulating strategies to cultivate a workforce well-prepared for the future. The study utilized different interrelated methodological approaches: scoping review and key informant interviews (KIIs), with distinct data-collection methods. The results of the scoping review and KIIs suggest there was no clear common definition of the concept or its dimensions. However, the Philippine articulations of TVCs commonly identify these three categories: (a) critical thinking and other cognitive skills, (b) interpersonal skills, and (c) intrapersonal skills. While these dimensions are prioritized, the data were less clear about what the priorities were in which TVC concepts and skills should be assessed. To lay the groundwork on potential assessments, a recommendation of the study involves a need to formulate a multicomponent assessment of soft skills aligned with basic and higher education curricula. Co-creating a systematic approach of developing assessments of TVCs may include stakeholder consultations, cost-benefit analyses, and meticulous test development phases to ensure technical expertise and appropriateness to local contexts. In the future, these assessments may also be leveraged for human resource development and learning in various employment sectors.
Keywords: 330; 21st century skills; soft skills; transversal competencies